Comparison of triple‐site ventricular pacing versus conventional cardiac resynchronization therapy in patients with systolic heart failure: A meta‐analysis of randomized and observational studies. Issue 1 (21st December 2017) - Zhang, Baowei; Guo, Junfang; Zhang, Guohui
Abstract: Background: Conventional cardiac resynchronization therapy (CRT, Bi‐V) is associated with no response in about 40% patients due to an insufficient resynchronization. Some studies showed triple‐site ventricular (Tri‐V) pacing had greater benefits compared with Bi‐V pacing, but the results of these studies were conflicting. We hypothesized that Tri‐V pacing had greater benefits on long‐term outcomes compared with Bi‐V pacing in patients with heart failure. Methods: PubMed, EMBASE, and the Cochrane Library were searched for clinical studies with related outcomes. Weighted mean differences (WMD) and 95% confidence intervals (CIs) were calculated to compare the change in left ventricular ejection fraction (LVEF), left ventricular geometry, functional capacity, and quality of life between Tri‐V pacing group and control group. Results: Five trials with 251 patients were included in the analysis. Patients in the Tri‐V pacing group had a greater improvement in LVEF (WMD 4.04; 95% CI 2.15‐5.92, P  < .001) and NYHA classes (WMD −0.27; 95% CI −0.42 to −0.11, P  = .001) compared with control group. However, there were no significant differences in left ventricular geometry, six‐min walk distance, or Minnesota Living With Heart Failure Questionnaire score between the two groups. The subgroup analyses showed there might be a greater improvement in LVEF in the Tri‐V pacing group in patients with QRS duration ≥ 155 ms (WMD 5.60; 95% CI 3.09‐8.10, P  < .001). Conclusions: The present analysis suggests that Tri‐V pacing has greater benefits in terms of an improvement in LVEF and functional capacity in patients with systolic heart failure, especially in patients with the duration of QRS ≥ 155 ms.